Cold urticaria and your risk of anaphylaxis - Paulo Eduardo Silva Belluco; Bárbara Garcia Sifuentes; Maurício Domingues Ferreira (Hospital de Clínicas de Itajubá, 2021)
Cold urticaria (CU) is characterized by the appearance of wheals or angioedema after exposure to cold. It presents with mild to severe symptoms and can even lead to anaphylaxis. The risk of systemic reactions is high. We discuss this important pathology and show its strong relationship with anaphylaxis. Cold weather is one of the most common triggers for the onset of symptoms, with variables including humidity and thermal sensation. It is divided into acquired or familial forms. The diagnosis is made in patients with a medical history suggestive of the disease and should be confirmed with a stimulation test. The central aspect of treatment is to avoid cold stimuli. The prescription of self-injectable epinephrine for groups that are at high risk of systemic reactions is ideal. In conclusion, health professionals should be aware of CU in order to recognize the risk of anaphylaxis in these patients.